Rating of Physics Laboratory Resources Management in Tertiary Institutions: Implications for Teaching and Learning STEM Subjects - Bada, Abiodun; Jita, Loyiso (Universitas Terbuka, 2021)
Physics, a major branch of science requires adequate implementation of its theoretical and practical components. The critical role played by the use of laboratory in realising this goal cannot be overemphasized hence, the need for proper management of laboratory resources. This study investigated the rating of physics laboratory resources management in tertiary institution and its implications for STEM subjects using student’s voice. The investigation adopted a descriptive-survey research design which comprised 596 students taking physics-related courses in six tertiary institutions in Ondo State. A questionnaire with 19 item statements was designed titled ‘Questionnaire on Physics Laboratory Resources Management’ (QPLRM) and used to collect data for this study. The data collected were analysed using mean scores and ranking. Inadequate funding to carry out managerial plans and lackadaisical attitude on the part of lecturers were rated highest to have hindered the proper management of physics laboratory resources for improving STEM subjects. The study concludes that adequate funding and improved positive attitude on the part of lecturers and support staff are important to guarantee proper teaching of STEM subjects. The study recommends that government through its agencies should provide more funds for the adequate implementation of STEM subjects.